Rumohra ponceana (Polypodiales: Dryopteridaceae): a new species from Pampean biogeographic province in Argentina - Arana, Marcelo D.; Luna, María Luján; Berrueta, Pedro C.; Martinenco, María Luz; Giudice, Gabriela E. (Phytotaxa, 2021)
The fern Rumohra ponceana sp. nov., a narrow endemic of the Austral Pampean district, Pampean biogeographic province in Argentina, is described and illustrated. The species inhabits the Tandilia and Ventania Systems, where it grows in sunny rock crevices. The new species differs from the widespread R. adiantiformis (sensu lato) by the reduced size of all parts of the sporophyte and conspicuous capitate glandular hairs at the margins of petiole and rhizome scales. Also, there are significant differences in the architecture of the laminae, the colour and size of the spores and the ornamentation of the perispore, which is folded in R. ponceana and projects in irregular tubercles throughout its surface.